Rancang Bangun High Gain Low Noise Amplifier Untuk Meningkatkan Sensitifitas Receiver Pada VHF Air Ground Communication - Muh Wildan; Ibnu Hermawan; Akhmad Prihandoyo (Approach : Jurnal Teknologi Penerbangan, 2017)
Radio receiver VHF A/G communication is a super heterodyne radio system, so that the radio system has a couple of blocks of the circuit and has own function. One part of the radio receiver is a Low Noise Amplifier (LNA). LNA is an important part of a radio receiver system and almost all communication equipment systems. LNA serves to strengthen the extremely weak signals captured by the antenna by adding a little bit of noise and minimize signal distortion. LNA has a specification that must be considered, such as stability, noise figure, gain, bandwidth, linearity, and dynamic range. Therefore, the LNA is very important, it is necessary to design the LNA. To increase the production of the gain can be done by designing a multistage LNA. This multistage LNA was designed using a voltage divider biasing. It was fabricated by using the Print Circuit Board with FR4 material or epoxy and using surface mounting device components. The operating point of amplifier at Ic = 5mA, VCC = 12V and VCE = 8V, requires power consumption DC by 151.2mW. This multistage LNA was simulated and the result of parameter in bandwidth show good performance and still meet the design specification. The value of parameter are stability factor in bandwidth was obtained 1.966-2.15 and noise figure 1.481-1.636dB, gain (S21) 40,168 until 43.28dB, reverse voltage gain (S12) -55.3dB until -53.53dB, output return loss (S22) below -9.4dB, at the center frequency 127.5MHz got S21=42.3dB, S11=-52.3dB, S22=-46.7dB, input VSWR=1.005 and output VSWR=1.01. This design has a good parameter and the corresponding design specifications, is expected to be applied to VHF A/G communication equipment in Sultan Bantilan Tolitoli Airport. By increasing the LNA gain can increase the sensitivity of the equipment VHF A/G communication so that air traffic controller and the pilot did not have communication problems.